Competence Based Training (CBT) Teknik Pengelasan Untuk Meningkatkan Keterampilan Taruna Teknika Kapal Niaga - Santosa, Prasetya Sigit; Astriawati, Ningrum; Wibowo, Waris; Pratama, Wegig (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
The high demand for competence in the world of the shipping industry today demands an increase in the skills of the Commercial Ship Engineering Study Program cadets, especially in the field of welding techniques. This indicates that Taruna's welding technique skills are still low. This Community Service Activity aims to improve welding technique skills and welding understanding for cadets. The Community Service Activity method uses the Competence-Based Training (CBT) Model, which combines theory, demonstration, and practicum. Evaluation is done by doing a pre-test, and post-test. CBT participants are 11th grade cadets of SMK Pelayaran Muhammadiyah 1 Kalasan Yogyakarta, with the expertise of Commercial Ship Engineering, with a total of 25 cadets. The results of the evaluation of Community Service were an increase of 60% in theory mastery, an increase of 64% in understanding demonstrations, and an increase of 84% in the skills of cadets in welding practice